Przygotowanie studentów uczelni muzycznych do pracy pedagogiczno-artystycznej = Preparation of music college students for pedagogical and artistic work - Kumik, Ewa (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
This article characterizes the law on the standards of education preparing for the teaching profession and presents the author?s model of pedagogical education of music college students implemented as part of the classes conducted at the Pedagogical College of the Music Academy of Grażyna and Kiejstut Bacewicz in Łódź.
Keywords: nauczyciel szkoły muzycznej; kształcenie pedagogiczne studentów; music school teacher; students' pedagogical education